Comparative study of nano and bulk Fe3O4 induced oxidative stress in Wistar rats. (4th July 2018) - Reddy, Utkarsh A.; Prabhakar, P. V.; Mahboob, Mohd
Abstract: Context: Magnetic nanomaterials (Fe3 O4 NMs) have become novel tools with multiple biological and medical applications because of their biocompatibility. However, adverse health effects of these NMs are of great interest to learn. Objective: This study was designed to assess the size and dose-dependent effects of Fe3 O4 NMs and its bulk on oxidative stress biomarkers after post–subacute treatment in female Wistar rats. Methods: Rats were daily administered with 30, 300 and 1000 mg/kg b.w. doses for 28 d of Fe3 O4 NMs and its bulk for biodistribution and histopathological studies. Results: Fe3 O4 NMs treatment caused significant increase in lipid peroxidation levels of treated rats. It was also observed that the NM treatment elicited significant changes in enzyme activities of superoxide dismutase, catalase, glutathione peroxidase, glutathione reductase and glutathione-S-transferase in treated rat organs with major reduction in glutathione content. Metal content analysis revealed that tissue deposition of NM in the organs was higher when compared to bulk and caused histological changes in liver. Conclusion: This study demonstrated that for same dose, NM showed higher bioaccumulation, oxidative stress and tissue damage than its bulk. The difference in toxic effect of Fe3 O4 nano and bulk could be related to their altered physicochemical properties.